Determinants of COVID-19 vaccine-induced myocarditis - Jessica Rose; Nicolas Hulscher; Peter A. McCullough (SAGE Publishing, 2024)
Background: Following the roll-out of the Pfizer-BioNTech BNT162b2, Moderna mRNA-1273, and Janssen Ad26.COV2.S coronavirus disease 2019 (COVID-19) injections in the United States, millions of individuals have reported adverse events (AEs) using the vaccine adverse events reports system (VAERS). The objective of this analysis is to describe the myocarditis data in VAERS and the COVID-19 vaccines as potential determinants of myocarditis. Methods: We used VAERS data to examine the frequency of reporting myocarditis since the beginning of the mass vaccination campaign and compared this with historical values in VAERS and COVID-19 vaccine administration data from the Our World in Data database. We examined myocarditis reports in VAERS in the context of sex, age, and dose. Statistical analysis was done using the Student's t- test to determine statistically significant differences between ages among myocarditis adverse events (AEs) and the chi-square test to determine relationships between categorical variables with statistical significance. Results: We found the number of myocarditis reports in VAERS after COVID-19 vaccination in 2021 was 223 times higher than the average of all vaccines combined for the past 30 years. This represented a 2500% increase in the absolute number of reports in the first year of the campaign when comparing historical values prior to 2021. Demographic data revealed that myocarditis occurred most in youths (50%) and males (69%). A total of 76% of cases resulted in emergency care and hospitalization. Of the total myocarditis reports, 92 individuals died (3%). Myocarditis was more likely after dose 2 ( p  < 0.00001) and individuals less than 30 years of age were more likely than individuals older than 30 to acquire myocarditis ( p  < 0.00001). Conclusion: COVID-19 vaccination is strongly associated with a serious adverse safety signal of myocarditis, particularly in children and young adults resulting in hospitalization and death. Further investigation into the underlying mechanisms of COVID-19 vaccine-induced myocarditis is imperative to create effective mitigation strategies and ensure the safety of COVID-19 vaccination programs across populations.